2016
DOI: 10.1007/5584_2016_171
|View full text |Cite
|
Sign up to set email alerts
|

The Simple and Unique Allosteric Machinery of Thermus caldophilus Lactate Dehydrogenase

Abstract: Many bacterial L-lactate dehydrogenases (LDH) are allosteric enzymes, and usually activated by fructose 1,6-bisphosphate (FBP) and often also by substrate pyruvate. The active and inactive state structures demonstrate that Thermus caldophilus, Lactobacillus casei, and Bifidobacterium longum LDHs consistently undergo allosteric transition according to Monod-Wyman-Changeux model, where the active (R) and inactive (T) states of the enzymes coexist in an allosteric equilibrium (pre-existing equilibrium) independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…These results show a direct correlation between the formation of the nuclei that leads to the native structure and ligand binding [10]. Numerous other examples have directly linked conformational states and binding [74][75][76][77]. Nevertheless, the PTP-BL PDZ2 analysis relates nonstable conformations (in the classical manner of open/close) but the folding process itself and binding.…”
Section: A Correlation Between Binding Affinity and The Folding Mechamentioning
confidence: 90%
“…These results show a direct correlation between the formation of the nuclei that leads to the native structure and ligand binding [10]. Numerous other examples have directly linked conformational states and binding [74][75][76][77]. Nevertheless, the PTP-BL PDZ2 analysis relates nonstable conformations (in the classical manner of open/close) but the folding process itself and binding.…”
Section: A Correlation Between Binding Affinity and The Folding Mechamentioning
confidence: 90%
“…Because of their dynamical properties and allosteric behaviour, Lactate Dehydrogenase (EC 1.1.1.27) (LDH) is an appropriate enzyme model to decipher the motions involved in the conformational changes that regulate enzyme catalytic activity2829. Recent studies have also shown that targeting eukaryotic LDHs with inhibitors, is an efficient way to treat epilepsy and cancers3031.…”
mentioning
confidence: 99%
“…LDHs are active tetramers of identical 30-35 kDa subunits. Most of the bacterial enzymes are allosteric displaying homotropic activation by the pyruvate and heterotopic activation by fructose 1,6-bisphosphate (FBP) (Taguchi, 2017). In contrast, eukaryotic LDHs are considered as non-allosteric.…”
Section: Introductionmentioning
confidence: 99%
“…To shed light on this peculiar phenomenon, we continued our investigations on Tt LDH by considering its allosteric properties. Indeed, Tt LDH is considered as a good representative of allosteric LDHs (Colletier et al, 2012;Coquelle et al, 2007;Taguchi, 2017). The native tetrameric state has four catalytic sites and two FBP-binding sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation